Rhodopsin targeted transcriptional silencing by DNA-binding - Salvatore Botta; Elena Marrocco; Nicola de Prisco; Fabiola Curion; Mario Renda; Martina Sofia; Mariangela Lupo; Annamaria Carissimo; Maria Laura Bacci; Carlo Gesualdo; Settimio Rossi; Francesca Simonelli; et al. (eLife, 2016)
Transcription factors (TFs) operate by the combined activity of their DNA-binding domains (DBDs) and effector domains (EDs) enabling the coordination of gene expression on a genomic scale. Here we show that in vivo delivery of an engineered DNA-binding protein uncoupled from the repressor domain can produce efficient and gene-specific transcriptional silencing. To interfere with RHODOPSIN (RHO) gain-of-function mutations we engineered the ZF6-DNA-binding protein (ZF6-DB) that targets 20 base pairs (bp) of a RHOcis-regulatory element (CRE) and demonstrate Rho specific transcriptional silencing upon adeno-associated viral (AAV) vector-mediated expression in photoreceptors. The data show that the 20 bp-long genomic DNA sequence is necessary for RHO expression and that photoreceptor delivery of the corresponding cognate synthetic trans-acting factor ZF6-DB without the intrinsic transcriptional repression properties of the canonical ED blocks Rho expression with negligible genome-wide transcript perturbations. The data support DNA-binding-mediated silencing as a novel mode to treat gain-of-function mutations.